How to do Climate change risk assessments in value chain projects - Vermeulen, Sonja J. (International Fund for Agricultural Development, 2015)
Successful value chain interventions that achieve poverty reduction goals can in themselves be beneficial to climate change adaption, as they build farmers’ assets and institutional linkages. But climate change can have major effects on the outcomes of IFAD-supported value chain interventions for smallholder beneficiaries; these outcomes may be negative or positive, and in many cases are uncertain. Therefore, it pays to do a simple upfront risk assessment to identify and manage risks and opportunities. The purpose of this How To Do Note (HTDN) is to provide guidance on the basics of climate risk analysis for value chain interventions. Farmers have dealt with climate risks throughout the entire history of agriculture. Climate change is now increasing the intensity, frequency and variety of those risks – and posing urgent new questions for IFAD's strategy and programming. Well over 50 per cent of IFAD-supported projects have a value chain development component (see How To Do Note: Designing commodity value chain development projects, IFAD, 2014). Climate-related risks can cause major losses of revenue for the sector. The livelihoods of smallholders tend to be most at risk. However, climate change also has the potential to offer new opportunities for some agricultural value chains – for example by opening up higher altitude areas for farming. In general, these gains need to be balanced against concerns regarding biodiversity conservation and soil erosion on steep slopes, and may be offset by increasing extreme weather events. Particular topics mentioned in this HTDN are covered in more depth in other IFAD toolkits, most importantly: Designing commodity value chain development projects (PTA, 2014) http://www.ifad.org/knotes/valuechain/index.htm. Climate-smart smallholder agriculture: What’s different? IFAD Occasional Paper 3 (ECD, 2012) http://www.ifad.org/pub/op/3.pdf. Impact of climate change on fisheries and aquaculture in the developing world and opportunities for adaptation (IFAD) http://www.ifad.org/lrkm/pub/fisheries.pdf